Polymyxins and Their Potential Next Generation as Therapeutic Antibiotics - Vaara, Martti (Frontiers in Microbiology, 2019)
The discovery of polymyxins, highly basic lipodecapeptides, was published independently by three laboratories in 1947. Their clinical use, however, was abandoned in the sixties because of nephrotoxicity and because better-tolerated drugs belonging to other antibiotic classes were discovered. Now polymyxins have resurged as the last-resort drugs against extremely multi-resistant strains, even though their nephrotoxicity forces clinicians to administer them at doses that are lower than those required for optimal efficacy. As their therapeutic windows are very narrow, the use of polymyxins has received lots of justified criticism. To address this criticism, consensus guidelines for the optimal use of polymyxins have just been published. Quite obviously, too, improved polymyxins with increased efficacy and lowered nephrotoxicity would be more than welcome. Over the last few years, more than USD 30 million of public money has been used in programs that aim at the design of novel polymyxin derivatives. This perspective article points out that polymyxins do have potential for further development and that the derivatives already now at hand might offer major advantages over the old polymyxins.